Best evidence topic: What is the best management of the appendix-stump in acute appendicitis: Simple ligation or stump invagination?. (December 2015) - Blake, Laura; Som, Robin
Abstract: A best evidence topic has been constructed using a described protocol. The three-part question addressed was: for patients undergoing appendicectomy for complicated acute appendicitis is simple ligation or invagination of the appendix-stump safer? Using the reported search, 587 papers were found. Five studies were deemed to be suitable to answer the question. In conclusion, the literature is more in favour of the appendix stump being managed with simple ligation rather than stump invagination. All 5 studies assessed are prospective, randomised studies, though overall the quality of these studies is poor. The outcomes assessed were incidence of post-operative complications (pyrexia, wound infection, abscess, caecal fistula and post-operative ileus), post-operative length of stay and mean operating time. The analysis indicates no significant difference between the groups in rates of post-operative pyrexia, intra-abdominal abscess or caecal fistula. Only one study showed a significant difference in rates of wound infection in favour of simple ligation. One study demonstrated a significant difference in favour of simple ligation when comparing rates of post-operative ileus. Overall, simple ligation was found to reduce patient length of stay when compared with stump invagination; one study found this difference to be significant. Simple ligation also produced shorter operating times compared with stump invagination – a risk factor for the development of post-operative ileus. All studies suffered limitations that make the quality of the evidence assessed poor. Although this evidence does favour simple ligation of the stump as compared to invagination, higher quality randomised studies are needed to answer the question definitively.